SYSTEMATIC LITERATURE REVIEW: MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) PADA PEMBELAJARAN MATEMATIKA - Hurin Nabilla; Nur Fitriyana (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2022)
This study aims to conduct literature on the Team Games Tournament (TGT) learning model in Mathematics learning and to identify the identification and aplication of the team games tournament learning model in mathematics learning. The method used in this study is systematic literature review (SLR) method. From a review of articles and research, the Team Games Tournament Learning Model in mathematics learning show that learning activities with the Team games tournament learning model in mathematics learning have a significant positive Effecton increasing student learning haul in understanding the concept of student responses and student activities being more effective. This is in line with the results of a review of several articles in which it is found that learning with the team games tournament learning model Can be used as an innovation in learning.